Strategic Marketing Plan for Mont Albo Massage Hut - Bustos, John Joshua O.; Concepcion, Charlene Louise V.; De Rosario, Jonas Phillip B.; Osite, Harry E. and Panis, Patricia Claire M., 2017 4 0 16; 5
Abstract: Mont Albo Massage Hut is a Filipino-inspired spa specializing in affordable traditional Filipino massages, body scrubs, and other spa treatments set in the modern spa setting. It started as a small massage clinic on March 11, 2007 in a old apartment in 6842 Washington St., Makati City and was established by a young doctor, Dr. Maynoll Montalbo, from Batangas City. The name Mont Albo was coined from the owner's surname Montalbo which means white mountain in Spanish. Being able to experience traditional Filipino healing practices since childhood, he became a firm believer of Hilot and various related forms of therapies. Now, the massage spa has more than 30 branches nationwide and a Superband in its name making it one of the most sought-after franchises in the country. The spa franchise belongs in the health and wellness service industry particularly wellness and spa centers with ages 25-64 as the industry market. The threat of new entrants is high as well as the bargaining power of buyers and rivalry among existing competitors while the bargaining power of suppliers and threat of substitute services are low. On the other hand, Mont Albo Massage Hut's markets are ages 25-54. Their main competitors are Nuat Thai, Wnsha Spa Center , and Zen Asia Wellness. This strategic marketing plan aims to increase the millennial market of Mont Albo Massage Hut especially those that belong in the ages 18-24 implementing strategies that capture their attention such as strong online presence through partnership with popular personalities and exiting sales promotion in the form of online raffles; and redesigning of facilities to make it more appealing to them. Moreover, the researchers give the Hilot an emphasis to maintain the company's uniqueness and edge from competitors.
Thesis: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2